An Unusual Cause of Recurrent Pneumonia in a Child - Manoj Madhusudan; Venkateswari Ramesh; Singaravelu Manikavasagam (Wolters Kluwer Medknow Publications, 2022)
Background: Recurrent pneumonia is defined as at least two episodes of pneumonia in a year or three episodes during a lifetime, with clinical and radiological improvement in between. Clinical Description: A 5-year and 8-month-old boy presented with a history of three episodes of fever and fast breathing of variable duration over 8 months. In between, he had a persistent moist cough with intermittent fever, weight loss, and darkening pigmentation. He had three prior admissions for the same, with X-rays showing multilobar pneumonia. Routine investigations were normal. Tuberculosis workup was negative. Computerized tomography showed changes in consolidation without any evidence of structural abnormality. The child became asymptomatic with short courses of antibiotics and nebulization during these admissions. He was referred to us for further evaluation, and we reviewed his history, examination, and medical records. Management: The darkened complexion was suggestive of Addisonian pigmentation, but serum electrolytes were normal. However, very low levels of morning cortisol and high adrenocorticotrophic hormone were suggestive of adrenal insufficiency. Retrospective history revealed dysphagia with nocturnal cough suggesting aspiration. Barium swallow confirmed achalasia by the presence of a dilated esophagus with distal narrowing. The clinical phenotype was suggestive of Triple A (AAA) syndrome with Addison's disease, alacrimia, and achalasia. A positive Schirmer's test confirmed alacrimia and established the clinical diagnosis. He was started on replacement hydrocortisone and later taken up for Laparoscopic Heller Myotomy with fundoplication. On follow-up, his appetite improved, his cough subsided, he had adequate weight gain, and the pigmentation had decreased. Conclusion: Achalasia should be considered a differential in recurrent pneumonia. AAA syndrome has isolated glucocorticoid deficiency. Therefore, hyperpigmentation in the presence of normal electrolytes should not preclude considering the possibility of adrenal insufficiency.